2001
DOI: 10.1097/00006416-200109000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Using the Internet for Patient Education

Abstract: The Internet, especially the World Wide Web, has a wealth of health-related information easily accessible to patients and families. Commercial health-related Internet sites offer the "3 C's: content, commerce, and connectivity. Many are quickly adding the 4th "C": communication. A growing concern among health care professionals is the quality and the seemingly overabundance of patient education information available on the Internet. Certainly it is possible for nurses to use the Internet for patient education,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…Despite the heavy use of web-based health information [9,10,15,24,31], only 12% of adults have the health literacy skills to navigate their health issues. According to the National Assessment of Adult Literacy [45], the mean reading level for adults in the United States is of an eighth grade level [21,22,43,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the heavy use of web-based health information [9,10,15,24,31], only 12% of adults have the health literacy skills to navigate their health issues. According to the National Assessment of Adult Literacy [45], the mean reading level for adults in the United States is of an eighth grade level [21,22,43,51].…”
Section: Discussionmentioning
confidence: 99%
“…Eight million individuals in the United States go online for health information everyday [24]. Studies have demonstrated orthopaedic patients use the Internet extensively for health education materials [9,10,15,31]. Patients likely also use online education materials without being able to discuss its content with an orthopaedic surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…The Web site reach as measured by number of daily unique visitors of more than 35,000 adds further credibility to our sample selection [2] (oral communication, Jim Ogale, AAOS Web site staff, June 6, 2007). Numerous authors report patients seeking orthopaedic care extensively use the Internet as a resource for patient education [8,9,13,28]. Access to the Internet and its use to obtain health information are increasing globally at a rapid pace.…”
Section: Discussionmentioning
confidence: 99%
“…Access to the Internet and its use to obtain health information are increasing globally at a rapid pace. One study reported three of every four patients attending an orthopaedic clinic have access to the Internet [13]. The Pew Research Center report found, in 2006 alone, more than 100 million people in the United States searched the Internet to find health information about diseases from which they or their relatives and friends suffer [20].…”
Section: Discussionmentioning
confidence: 99%
“…Una buena alternativa para conseguirlo es utilizar folletos o documentos escritos que se entregan y se pueden consultar tras el alta hospitalaria. Los materiales impresos son económicos, sencillos de transportar y con contenidos fáciles de usar y mantener 12 . Sin embargo, para que la información contenida en estos documentos sea efectiva debe ser entendida por las personas a las que va destinada 13 .…”
unclassified